(untitled) (Texas Journal of Engineering and Technology, 2026)
Micro hydropower plants (micro-HPPs) play a significant role in providing reliable and sustainable electricity to remote and rural areas. However, one of the main challenges in micro-HPP operation is maintaining stable voltage and frequency under variable load conditions. Traditional ballast load controllers dissipate excess energy as heat, leading to efficiency losses. This paper proposes an improved structural configuration and operating algorithm for a micro hydropower plant with a batterybased ballast load. The proposed system combines an electronic load controller with a battery energy storage system to absorb surplus power, enhance energy utilization, and stabilize operating parameters. The developed control algorithm ensures frequency regulation, optimal battery charging and discharging, and reliable operation of the asynchronous generator. Simulation-based analysis demonstrates that the proposed approach significantly improves overall system efficiency, power quality, and operational flexibility